2014
DOI: 10.1128/jb.01824-14
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate Increases Binding Affinity of Vibrio cholerae ToxT to Virulence Gene Promoters

Abstract: The major Vibrio cholerae virulence gene transcription activator, ToxT, is responsible for the production of the diarrhea-inducing cholera toxin (CT) and the major colonization factor, toxin coregulated pilus (TCP). In addition to the two primary virulence factors mentioned, ToxT is responsible for the activation of accessory virulence genes, such as aldA, tagA, acfA, acfD, tcpI, and tarAB. ToxT activity is negatively modulated by bile and unsaturated fatty acids found in the upper small intestine. Conversely,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…Autoradiographs were analyzed using ImageJ software (NIH) as previously described, with nonspecific binding omitted from further analysis (32). Briefly, to determine the K D (equilibrium dissociation constant) for samples containing either linoleic acid or virstatin and compared to protein bound to DNA without inhibitor, the percentage of protein bound with labeled DNA was determined for each lane.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Autoradiographs were analyzed using ImageJ software (NIH) as previously described, with nonspecific binding omitted from further analysis (32). Briefly, to determine the K D (equilibrium dissociation constant) for samples containing either linoleic acid or virstatin and compared to protein bound to DNA without inhibitor, the percentage of protein bound with labeled DNA was determined for each lane.…”
Section: Methodsmentioning
confidence: 99%
“…Strains were maintained in Luria broth (LB) containing 20% glycerol and stored at Ϫ70°C. All promoter::lacZ fusions used for ␤-galactosidase assays were made in plasmid pTL61T as described for previous studies (26,32). Overnight cultures were grown for ϳ16 h at 37°C in LB and then diluted 1:40 into LB (pH 6.5) at 30°C for virulence-inducing conditions in the presence or absence of freshly prepared 0.05% bile (sodium choleate), 160 M linoleic acid, or 100 M virstatin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has suggested that palmitoleic acid decreases the ability of ToxT to bind to P tcpA (19). Additionally, we have shown that bicarbonate increases the binding affinity of ToxT to virulence gene promoters regardless of toxbox orientation (37). To assess the ability of linoleic acid and bicarbonate to alter the binding affinity of ToxT N106F to P tcpA , we used electrophoretic mobility shift assays (EMSAs) to determine the equilibrium binding affinity of WT MBP-ToxT and the N106F derivative for the major virulence gene promoter, P tcpA , in the absence and presence of effector.…”
Section: Identification Of Toxt Residues Involved In Responding Tomentioning
confidence: 55%
“…Autoradiographs were analyzed using ImageJ software (NIH) as previously described (37). Briefly, the percentage of labeled DNA bound by MBP-ToxT WT or N106F was determined for each lane, and GraphPad Prism 5 software was used for curve fitting to the…”
Section: Methodsmentioning
confidence: 99%